2006
DOI: 10.1111/j.1468-2958.2006.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Comforting Process Work? An Empirical Test of an Appraisal-Based Model of Comforting

Abstract: Burleson and Goldsmith's (1998) comforting model suggests an appraisal-based mechanism through which comforting messages can bring about a positive change in emotional states. This study is a first empirical test of three causal linkages implied by the appraisal-based comforting model. Participants (N = 258) talked about an upsetting event with a confederate trained to display low, moderate, or high levels of person centeredness and nonverbal immediacy. After the conversation, participants completed several sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
4
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(199 citation statements)
references
References 55 publications
16
175
4
3
Order By: Relevance
“…The more Max leans forward to place objects near his partner, the more Max expresses his empathy. This is in agreement with Jones and Wirtz [12], who state that human approach behaviors such as leaning forward, have been shown to convey positive affect, involvement and liking. While this paper focuses more on the technical details of the proposed approach, in future work an evaluation of this approach is planned to investigate how Max's modulated helping actions impact a human partner's engagement in achieving a successful cooperation.…”
Section: Discussionsupporting
confidence: 91%
“…The more Max leans forward to place objects near his partner, the more Max expresses his empathy. This is in agreement with Jones and Wirtz [12], who state that human approach behaviors such as leaning forward, have been shown to convey positive affect, involvement and liking. While this paper focuses more on the technical details of the proposed approach, in future work an evaluation of this approach is planned to investigate how Max's modulated helping actions impact a human partner's engagement in achieving a successful cooperation.…”
Section: Discussionsupporting
confidence: 91%
“…The modest effects observed for personality and situational factors in the current studies (as well as for demographic factors in previous studies), in conjunction with the large effects observed for message person centeredness, suggest that messages with different levels of person centeredness exert differential effects on recipients because they impact underlying cognitive and emotional processes in recipients. More specifically, it does not appear that HPC messages are simply conventional devices within certain social groups for indicating care and concern; rather, these messages appear to influence how recipients think about their feelings and the circumstances producing those feelings (Burleson & Goldsmith, 1998;Jones & Wirtz, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, little research has used experimental procedures (cf. Jones & Wirtz, 2006) to assess the impact of discussing difficult issues over time, despite the fact that friends often discuss difficulty more than once (e.g., Rose, 2002). Thus, in the current study, we expand on evidence from both the EWP and social support literature and pose the following research question to examine the impact of listening to friends' stories of difficulty over time:…”
Section: The Benefits and Risks Of Providing Supportmentioning
confidence: 99%